Anode coke from coal – A low cost approach. (1st January 2017) - Craddock, John D.; Rantell, Terry D.; Hower, James C.; Whitlow, David T.; Wiseman, John; Weisenberger, Matthew C.
Abstract: Declining quality and availability of petroleum cokes, which have traditionally been used for the production of carbon anodes, is forcing aluminum producers to use cokes previously regarded as unsuitable. Domestic reserves of coal represent a potential alternative carbon resource for anode production, provided coke specifications can be economically achieved. Previous studies have shown that the solvent refining of coal could produce carbons suitable for aluminum production. To conform to coke specifications (e.g. metals content), it was necessary to remove mineral matter in the coal by a costly filtration step. This adds significantly to the cost of the process, making it uncompetitive with coke from other sources. However, cokes with properties very similar to the required specifications have been produced from very low ash coals by solvent extraction, but without the uneconomic solids removal step. Extraction in a suitable solvent was used to produce a coal digest, which when injected at high temperature into a coking vessel generated the anisotropic needle structure characteristic of high quality cokes. Reported herein are the results of our investigation into using low-ash coals (1–2 wt.%) from the southeastern Kentucky coalfield to produce anode-grade cokes using similar methods. The high cost filtration step was omitted, but the resulting coke did not meet the anode grade specifications.